Digitalization of Financial Reporting as a Means to Fulfill Tax Obligations - Santi, Fitriana; Puspita, Wulan Dri; June, Cindy Getah Trisna; Agesia, Sheina Vella (Institut Teknologi Nasional, Bandung, 2024)
Financial statements are an accounting product that remains a major challenge in the financial performance of Micro, Small, and Medium Enterprises (MSMEs). It is still common to find MSMEs, even those with substantial turnover, lacking financial statements. However, every MSME operator, whether online or offline, is required to report their taxable income. The amount of tax owed can be determined if business owners have an income statement. CV Sinama, a skincare business, is one example that lacks financial statements and has not reported taxes. Based on this issue, the objective of the community service was to train in digital financial reporting (using spreadsheets) and online tax reporting. The results of the community service show that partners have been able to prepare and calculate profit and loss statements. The profit figures are used as the basis for calculating the amount of tax owed.CV Sinama is now able to prepare financial statements and determine the amount of corporate tax owed.